MASALAH-MASALAH YAN G DIHADAPI SISWA DALAM PEMBELAJARAN SEJARAH KELAS XI IPS Dl SlIA SEMEN PADANG - NINGSIH, SURYA FATMI ADE (Pendidikan Sejarah, 2014)
This research results in the wake of the low student studying history in social studies class XI at Semen Padang senior high school. Thi s study aims to I) describe the problems faced by students in learning the history of class XI social 2 and X I social 3 semester January-Jun e period of the academic year 2013/2014 at SMA Semen Padang and , 2) descnbe the factors that influence the effect of the problems of students in learning the history of class Xl social 2 and XI social 3 semester January-June period of the academic year 2013/2014 at SMA Semen Padang . The method used in this research is descriptive qualitative. The results of tbis research showed about the problems faced by students in learning history consists of, the internal and external problems . Internal problems experienced by students in learning history consists of, ( I) many student that low interested to learning hi story. Caused by the intelligence factor and factor methods. (2) poor to attention or follow the learning activity. Caused by an interest fac1or and factor methods. (3) poor concentration i n learning. Caused by a factor of motivation and school time. (4) did not repeated the lesson at home. Caused by friends. Moreover, external factors consist of,(I) the effect of the socia l environment. Caused by a student friend , at home and school.(2) l ess faci litate and infrastructure that use in learning history because most of teacher onl y use one reference in teaching learning process. Thi s problems caused due to lack of use media in learning.